Sām-nāma - Kirmānī, Khwāju-yi, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persian literary history, Firdawsī's (d. 411/1020) Shāh-nāma , the famous masnavi composed in celebration of the history of the kings and dynasties of Persia, is the archetypal epic poem. After the Shāh-nāma , many other epic poems saw the light, among them Asadī Ṭūsī's Garshāsp-nāma (dated 458/1066) and Īrānshāh b. Abi ʼl-Khayr's Bahman-nāma (dated 501/1107-08), but also Shīʿī adaptations celebrating the wondrous exploits of ʿAlī b. Abī Ṭālib and the beginnings of Shīʿism, such as Rabīʿ's ʿAlī-nāma (dated 482/1089) or Ibn Ḥusām's Khawarān-nāma (completed in 830/1427). The present masnavi is an example of an epic poem in the form of a romance, turning around the love of Sām, the grandfather of Rustam, for the daughter of the emperor of China. Previously ascribed to the 8th/14th-century poet Khwāju-yi Kirmānī, it has now been established that it is a product of later Persian folklore, blending parts of Kirmānī's Humāy u Humāyūn with elements from other tales and romances.